Advances in Grid and Pervasive Computing 6th International Conference, GPC 2011, Oulu, Finland, May 11-13, 2011. Proceedings - Riekki, Jukka; Ylianttila, Mika; Guo, Minyi (Springer eBooks., 2011)
This book constitutes the proceedings of the 6th International Conference, GPC 2011, held in Oulu, Finland in May 2011. The 28 revised full papers were carefully revised and selected from 62 submissions and focus on the topics cloud, cluster, and grid computing; peer-to-peer computing; applications and HCI; modeling and verification; service architectures; middleware; and sensor networks.